2018
DOI: 10.14710/jdep.1.1.1-13
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Inklusi Keuangan Di Indonesia (Global Findex 2014)

Abstract: Financial inclusion has been a trend since post 2008 crisis especially derived from the effects of the crisis towards the class in the bottom of the pyramid. Financial inclusion rate in Indonesia, if seen from three main indicators, is still low. Indonesians who have an account in financial institutions is at 35,95 percent and those who save is at 25,56 percent. Meanwhile, Indonesians who borrow in formal financial institutions are only at 13,3 percent. This study aims to examine individual characteristics in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 1 publication
6
23
2
3
Order By: Relevance
“…Other characteristics, such as gender, education index, and occupation do not significantly influence the financial inclusion index. It corresponds with a study by Nugroho & Purwanti (2014) that the higher the index of income, the higher the probability of having bank accounts and depositing money in the formal financial institution. Further explanation reveals that income index increases, not all goes to consumption, but to other aspects, i.e., accessing financial services.…”
Section: |supporting
confidence: 65%
“…Other characteristics, such as gender, education index, and occupation do not significantly influence the financial inclusion index. It corresponds with a study by Nugroho & Purwanti (2014) that the higher the index of income, the higher the probability of having bank accounts and depositing money in the formal financial institution. Further explanation reveals that income index increases, not all goes to consumption, but to other aspects, i.e., accessing financial services.…”
Section: |supporting
confidence: 65%
“…So that financial activities will be mostly done by men. Nugroho (2017), who found that gender did not affect decisions on account ownership, saving, and borrowing informal financial institutions. However, this result was supported by Perpres No.…”
Section: The Gender Factor For Financial Inclusionmentioning
confidence: 99%
“…It shows that Fintech product have succeed to become an alternative for Muslims entrepreneur to get financial inclusion. By the Fintech existence challenges of financial inclusion such as access restriction to formal financial institution, lack of knowledge, and product complexity offered by financial institution can be solved (Nugroho & Purwanti, 2018) It is in accordance with the Financial Services Authority (OJK) aspiration in National Strategy on Indonesian Financial Literacy (SNLKI) that push Fintech to take a role in providing financial inclusion (Otoritas Jasa Keuangan, 2017).…”
Section: Fintech Relation On Financial Inclusionmentioning
confidence: 99%
“…One of the obstacles to increase Indonesia's financial inclusion index is the access to formal financial institution were low because of the lack of knowledge and product complexity offered by financial institution (Nugroho & Purwanti, 2018). This is supported by a survey of national financial literacy conducted by The Financial Services Authority (OJK) in 2013 to 2016, there is improvement of financial inclusion index, from 59.7% to 67.8% in 2016 (Otoritas Jasa Keuangan, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation